Influence of Leader’s Demographic Characteristics and Perspective towards Implementation of NGOs’ Gender Parity Strategies in Secondary School of Kibera Informal Settlement - Alusa, Mwarili Margaret (American Journal of Education and Learning, 2018)
This study investigated the influence of leader’s demographic characteristics and perspectives towards implementation of gender parity strategies (GPS) in secondary schools of Kibera informal settlement, Kenya. The study was guided by Adams Stacy’s equity theory and Herzberg’s two-factor theory. The study utilized survey design. It targeted leaders of secondary schools managed by Non-Governmental Organizations (NGOs). Purposive sampling was utilized to select the schools, while stratified and simple random sampling was used to select the respondents. Data were collected by use of a questionnaire. Data analysis techniques included Chi-square, regression, and ANOVA. The study established that the demographic characteristics; age, academic qualification and experience influenced the leader’s implementation of NGOs’ gender parity strategies (p<0.05). Additionally, the perspective of the leaders also influenced positively the leader’s implementation of NGOs’ gender parity strategies (p<0.05). This study will contribute to the preparedness of the education stakeholders in addressing gender disparities gap in secondary schools, it will intensify the extent of involvement of NGOs and other education stakeholders in supporting the efforts towards attainment of EFA goals and Sustainable Global gender parity educational goals. The study will enlighten education stakeholders on measures and strategies of minimizing gender disparities gap in secondary education in informal settlements of Kenya.